2022
DOI: 10.3389/fimmu.2022.900509
|View full text |Cite
|
Sign up to set email alerts
|

Promising Acinetobacter baumannii Vaccine Candidates and Drug Targets in Recent Years

Abstract: In parallel to the uncontrolled use of antibiotics, the emergence of multidrug-resistant bacteria, like Acinetobacter baumannii, has posed a severe threat. A. baumannii predominates in the nosocomial setting due to its ability to persist in hospitals and survive antibiotic treatment, thereby eventually leading to an increasing prevalence and mortality due to its infection. With the increasing spectra of drug resistance and the incessant collapse of newly discovered antibiotics, new therapeutic countermeasures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 150 publications
0
7
0
Order By: Relevance
“…Because most A. baumannii strains are multidrug-resistant, the use of multiple antibiotics often is still not sufficient to treat infection, and for this reason, it has been suggested that new therapies and more well-controlled studies are needed to study possible treatment options, as well as placing a greater emphasis on the prevention of infection transmission [ 13 ]. In line with this vision, the World Health Organization has declared A. baumannii a top priority for the development of new medical countermeasures, such as a vaccine, [ 64 ] and work toward such a vaccine is indeed underway, [ 65 ] although no vaccine has been developed sufficiently to the point of human clinical trials to date [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because most A. baumannii strains are multidrug-resistant, the use of multiple antibiotics often is still not sufficient to treat infection, and for this reason, it has been suggested that new therapies and more well-controlled studies are needed to study possible treatment options, as well as placing a greater emphasis on the prevention of infection transmission [ 13 ]. In line with this vision, the World Health Organization has declared A. baumannii a top priority for the development of new medical countermeasures, such as a vaccine, [ 64 ] and work toward such a vaccine is indeed underway, [ 65 ] although no vaccine has been developed sufficiently to the point of human clinical trials to date [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a reverse vaccinology study, a dataset of A. baumannii whole genomes investigated to identify the new putative vaccine candidates and selected DcaP-like protein and HP-2 as candidates among 11 ( 41 ). Overall, there are many different approaches to investigate the vaccine candidates both immunoinformatic and other omics strategies, which are extensively reviewed ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on traditional methods and platforms, such as subunit and killed vaccines. However, there are ongoing explorations of novel antigen transporters and enhanced delivery mechanisms, including nucleic acid vaccines, virus vectors, conjugated carriers, and co-delivery [ 21 , 113 , 117 ]. It is worth noting that mRNA and DNA vaccine technologies have gained significant recognition due to the competition surrounding COVID-19 vaccines.…”
Section: Lessons Learned and Future Perspectivesmentioning
confidence: 99%
“…Before advancing to clinical trials, vaccine candidates must undergo testing in experimental animals to assess reactogenicity and immune response [ 20 ]. Furthermore, it is essential to evaluate the pharmacological and toxicological properties of the targeted vaccine candidates to ensure their safety and efficacy [ 21 ]. This review investigates the spread of multidrug-resistant A. baumannii infections in healthcare settings in Saudi Arabia and explores potential measures to prevent their transmission.…”
Section: Introductionmentioning
confidence: 99%